PERANCANGAN PROTOTYPE SISTEM PENDETEKSI KONDISI TELUR DAN BERAT BERBASIS MIKROKONTROLER ARDUINO UNO - Rehandra Igo Nanda; Edidas Edidas (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2019)
The purpose of this research can facilitate the sorting of chicken eggs by the breeder automatically so as not to cause negligence in sorting chicken eggs, this tool is made to facilitate human work in the livestock industry, namely in the process of sorting chicken eggs. The process of designing and manufacturing systems have several stages, namely system design, hardware design, software design, and physical design. The results of the design and manufacture of this egg condition detection system can work by using the Arduino Uno microcontroller as the controller. This tool uses the LDR sensor to function as a detector of the intensity of light from the egg, then the ultrasonic sensor will detect the eggs that pass, then the eggs will be calculated by using the Load Cell sensor. Eggs will be separated based on conditions that have been detected by the LDR sensor and Arduino gives commands to the servo motor to separate good eggs and bad eggs, then automatically Arduino will send data to the LCD to display. From the results of this  research that this tool can separate which eggs are good and eggs are bad.Keywords: Arduino UNO, Sensor LDR, LED, Load Cell, Servo Motor, LCD